Effect of Aloe gel and cactus mucilage coating on chemical quality and sensory attributes of mango (Mangifera indica L.) - Abera, Nigusu Girma; Kebede, Weldetsadik; Wassu, Mohammed (Journal of Postharvest Technology, 2019)
Mango (Mangifera indica L.) is among major fruit crops grown in eastern Ethiopia. However, the postharvest handling problem contributes to huge postharvest loss of fruits. This experiment was conducted to study the effect of coating with Aloe gel and cactus mucilage on sensory and chemical quality of mango fruit. The experiment was laid out in completely randomized design (CRD) with three replications. The results revealed the significant effect of coating with aloe gel and cactus mucilage on most parameters considered. The interaction of aloe gel coating and storage period significantly influenced TSS, TA and sugar to acid ratio, while the interaction of cactus mucilage and storage period had significant effect only on TSS of mango juice. The aloe gel had significant effect on all sensory attributes while cactus only on color, appearance and over all acceptances. Generally, coating of mango fruits with aloe gel and cactus mucilage at 50 and 75% concentration level retard quality deterioration and keep good appearance. Therefore, coating of mango fruits with these extracts in combination and alone at higher concentrations could be used as alternative postharvest loss management of mango fruit. However, work requires replication in terms of cultivars, harvesting stage and different types of coatings.